Analysis of Special Methods and Sources of Tafsir in Tafsir Al-Mizan in Surah Al-Qari'ah by Muhammad Husain Thabathaba'i - Wahyu Muhammad Abdul Wahid; Putri Mega Shintia; Eni Zulaiha; Wildan Taufiq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the sources of interpretation, general and specific methods used by as-Sayyid Muhammad Husain Thabāthaba’i in the book al-Mizan fi Tafsir al-Quran especially in the interpretation of Surah Al-Al-Qari’ah. This research is a qualitative study with a descriptive method, using primary data from the Tafsir book and secondary data from related books and scientific articles. Tafsir al-Mizan is a phenomenal work of Muhammad Husain Thabāthaba’i. His work is inseparable from the thoughts of the author who has a background of thought that is based on the ideological teachings he adheres to, namely Shia. Even so, the Tafsir uses the uslub of the Qur'an bil Qur'an and also contains many opinions of other commentators. So that the Tafsir is called a very complete Tafsir because it contains many fields of science. The special manhaj or method of writing Tafsir al-Mizan is to interpret the book sequentially in the mushafy, explaining the general picture and purpose of the letter or verse being interpreted, when interpreting a particular letter or verse citing the opinions of Al-Qur'an reviewers and also explaining their own opinions, having a separate section on the discussion of narrations, specializing in the discussion of philosophical aspects, and providing a general conclusion from the verse or letter being studied.